Cytokines and STATs in Liver Fibrosis - Kong, Xiaoni; Horiguchi, Norio; Mori, Masatomo; Gao, Bin (Frontiers in Physiology, 2012)
Liver fibrosis, or cirrhosis, is a common end-stage condition of many chronic liver diseases after incomplete recovery from hepatocyte damage. During fibrosis progression, hepatocellular damage and inflammation trigger complex cellular events that result in collagen deposition and the disruption of the normal liver architecture. Hepatic stellate cell activation and transdifferentiation into myofibroblasts are key events in liver fibrogenesis. Research findings from cell culture and animal models have revealed that the Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway, which can be activated by many cytokines, growth factors, and hormones, plays a critical role in hepatic fibrogenesis. This review summarizes the biological significance of diverse cytokines and their downstream signaling protein STATs in hepatic fibrogenesis.